Effects of traffic lights for Manhattan-like urban traffic network inintelligent transportation systems. Issue 1 (2nd January 2018) - Chen, Bokui; Wang, David Z. W.; Gao, Yachun; Zhang, Kai; Miao, Lixin; Wang, Binghong
ABSTRACT: Traffic light is the core part of advanced transportation management systems. Assuming travelers receive and follow the route guidance information designed by two specific route choice strategies, this paper investigates how the traffic lights rule, period and its quantity affect the traffic system performance on a Manhattan-like urban network. Firstly, the simulation results of the average flow against the traffic density and the vehicle distribution are studied under four traffic light rules. Then the relationship between the extremum of average speed and traffic light period is complementally analyzed and the theoretical results have been proved basically in agreement with the simulation results. Lastly, the effects of the number of traffic lights on average flow and vehicle distribution are discussed. From these results, it is concluded that the traffic system performance can be improved if the anticlockwise rule combined with the congestion coefficient feedback strategy-based route guidance is adopted and the number of traffic lights is reduced to its minimum requirement.